Global prevalence of WHO infant feeding practices in 57 LMICs in 2010-2018 and time trends since 2000 for 44 LMICs - Zong Xin'nan; Wu Han; Zhao Min; Magnussen Costan G.; Xi Bo (United Kingdom, 2022)
Background
The World Health Assembly set a global target of increasing exclusive breastfeeding for infants under 6 months to at least 50% by year 2025. However, little is known about the current status of breastfeeding practice, as well as the trends in breastfeeding practices during recent years. We examined global prevalence of the World Health Organization (WHO) feeding practices in 57 low- and middle-income countries (LMICs) and time trends since 2000 for 44 selected countries.
Methods
We included 57 eligible LMICs that had completed data on breastfeeding and complementary feeding in 2010–2018 from the Demographic and Health Surveys (DHS) for examining current feeding status. We further selected 44 LMICs that had two standard DHS surveys between 2000 and 2009 and 2010–2018 to examine time trends of feeding status. We calculated global, regional, and national weighted prevalence estimates and 95% confidence intervals (CIs) for five breastfeeding indicators and two complementary feeding indicators.
Findings
In 57 LMICs during 2010–2018, global weighted prevalence was 51.9% for early initiation of breastfeeding, 45.7% for exclusive breastfeeding under 6 months, 32.0% for exclusive breastfeeding at 4–5 months, 83.1% for continued breastfeeding at 1 year, 56.2% for continued breastfeeding at 2 years, 14.9% for introduction of solid, semi-solid or soft foods under 6 months, and 63.1% for introduction of solid, semi-solid or soft foods at 6–8 months. Eastern Mediterranean (34.5%) and European regions (43.7%) (vs. South-East Asia/Western Pacific (55.2%)), and upper middle-income countries (38.4%) (vs. lower middle-income countries (47.4%)) had poorer performance of exclusive breastfeeding under 6 months. South-East Asia/Western Pacific regions (51.0%) (vs. other regions (68.3%-84.1%)) and low-income (66.4%) or lower middle-income countries (58.2%) (vs. upper middle-income countries (81.7%)) had lower prevalence of introduction of solid, semi-solid or soft foods at 6–8 months. In 44 selected LMICs from 2000 to 2009 to 2010–2018, total weighted prevalence presented an increase of 10.1% for exclusive breastfeeding under 6 months, but a 1.7% decrease for continued breastfeeding at 1 year. Over this period, the Eastern Mediterranean region had a 5.3% decrease of exclusive breastfeeding under 6 months, and the European region had a 2.0% increase for introduction of solid, semi-solid or soft foods under 6 months. The prevalence of introduction of solid, semi-solid or soft foods at 6–8 months decreased in South-East Asia/Western Pacific region by 15.2%, and in lower middle-income countries by 24.4%.
Interpretation
Breastfeeding practices in LMICs have continued to improve in the past decade globally, but practices still lag behind the WHO feeding recommendations. Breastfeeding practices differed greatly across WHO regions, with the Eastern Mediterranean and European regions, and upper middle-income countries facing the greatest challenges in meeting targets. Continued efforts are needed to achieve the 2025 global breastfeeding target.